Prevalence of and Risk Factors for Skin Diseases Among Army Personnel and Flood Victims During the 2011 Floods in Thailand. (17th February 2016) - Thongtaeparak, Wittaya; Pratchyapruit, Walai-orn; Kotanivong, Settha; Sirithanakit, Nimit; Thunyaharn, Sudaluck; Rangsin, Ram; Chaikaew, Phachara; Wongyongsin, Pitee; Pinyoboon, Pongpak; Sutthiwan, Phatcharaphan; Theethansiri, Witchwaree; Janthayanont, Dusit; et al.
Abstract: Objective: This study aimed to determine the prevalence of and risk factors for skin problems among flood victims and army personnel during the 2011 floods in Thailand. Methods: To determine the prevalence of and risk factors for skin symptoms, standardized questionnaires were used to collect demographic data, current skin symptoms, history of water exposure, and sanitary behaviors. A certified dermatologist evaluated those who presented with skin problems and provided diagnoses. Univariate and multivariate analyses were performed to assess independent risk factors for skin symptoms. Results: The most prevalent skin disease was irritant contact dermatitis. Flood victims showed a higher prevalence of skin symptoms compared with army personnel. Development of skin symptoms after exposure to floodwater was also observed earlier among flood victims. Having a history of skin diseases and delayed skin cleaning after exposure were also significant risk factors for the development of skin symptoms. Conclusion: This information might be used as guidelines for protecting military personnel and to educate the general public regarding flood disaster management. ( Disaster Med Public Health Preparedness . 2016;10:570–575)